2018
DOI: 10.1063/1.5024103
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of separator effect and shift angle on crossflow wind turbine performance

Abstract: The study of the influence of the diameter ratio and blade number to the performance of the cross flow wind turbine by using 2D computational fluid dynamics modeling AIP Conference Proceedings 1931, 030034 (2018) danar1405@gmail.comAbstract. This paper present experimental test results of separator and shift angle influence on Crossflow vertical axis wind turbine. Modification by using a separator and shift angle is expected to improve the thrust on the blade so as to improve the efficiency. The design of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Several studies have reported better performance for multi-stage turbines than conventional single-stage designs. Due to the effectiveness of multi-stage turbines, Fahrudin et al [119] conducted an experimental study to investigate the effect of multi-stage CFWTs on wind energy extraction. They have tested three types of rotors (single-stage, double-stage, and triple-stage) with different phase shift angles of 0 • , 6 • , and 12 • in the wind tunnel at wind speeds of 3 to 4.85 m/s.…”
Section: Number Of Stagesmentioning
confidence: 99%
“…Several studies have reported better performance for multi-stage turbines than conventional single-stage designs. Due to the effectiveness of multi-stage turbines, Fahrudin et al [119] conducted an experimental study to investigate the effect of multi-stage CFWTs on wind energy extraction. They have tested three types of rotors (single-stage, double-stage, and triple-stage) with different phase shift angles of 0 • , 6 • , and 12 • in the wind tunnel at wind speeds of 3 to 4.85 m/s.…”
Section: Number Of Stagesmentioning
confidence: 99%